Self-reported psychological characteristics as risk factors for injuries in female youth football - Steffen, K.; Pensgaard, A. M.; Bahr, R. (Scandinavian Journal of Medicine & Science in Sports, 2009)
Identifying and understanding injury risk factors are necessary to target the injury-prone athlete and develop injury prevention measurements. The influence of psychological factors on injuries in football is poorly documented. The purpose of this 8-month prospective cohort study therefore was to examine whether psychological player characteristics assessed by a self-administered questionnaire represent risk factors for injury. At baseline, female football players (14-16 years) were asked to complete a detailed questionnaire covering player history, previous injuries, perception of success and motivational climate, life stress, anxiety and coping strategies. During the 2005 season, a total of 1430 players were followed up to record injuries. A history of a previous injury [odds ratio (OR)=1.9 (1.4; 2.5), P<0.001] increased the risk of a new injury to the same region. There were significant differences in disfavor for previously injured compared with non-injured players for ego orientation (P=0.007), perception of a performance climate (P=0.003) and experienced stressful life events (P<0.001). However, only high life stress (P=0.001) and perception of a mastery climate (P=0.03) were significant risk factors for new injuries. In conclusion, a perceived mastery climate and a high level of life stress were significant predictors for new injuries in a cohort of young female football players.